Rare and First Manifestation of Lupus Panniculitis as Lupus Mastitis: A Case Report and Literature Review - Guo, Chong Yong; Chen, Li; Sun, Lin; Yang, Xiao Shan; Mao, Ruiqi; Li, Bo Cheng; Li, Xin Jun; Zhou, Ling (Current Medical Imaging, 2024)
Introduction This case report presents a rare occurrence of lupus mastitis affecting the breast. Case Presentation An induration with mild discomfort was detected in the upper inner quadrant of the right breast of a 27-year-old Chinese woman with regular menstrual cycles. The patient is currently unmarried and has no previous history of full-term pregnancies or lactation. An ill-defined, subcutaneous, hyperechoic lesion with no calcification was visualized on breast ultrasound. Peripheral and internal blood flow signals demonstrated high intensity. Pathological analysis of a breast needle biopsy revealed fat lobule necrosis accompanied by mixed lymphoplasmacytic and histiocytic aggregates. Conclusion The diagnosis of lupus mastitis necessitates a comprehensive evaluation of the patient's medical history, serological testing, imaging studies, and histopathological analysis.
Keywords: Systemic lupus erythematous